Removal of cesium ions from aqueous solutions using various separation technologies - Wang, Jianlong; Zhuang, Shuting (Reviews in environmental science and biotechnology, 2019)
Cesium is the major fission product of uranium, which widely exists in radioactive wastewater. Radiocesium has potential adverse effects on human health and ecological environment. Different methods such as chemical precipitation, coagulation/co-precipitation, solvent extraction, membrane process, chemical reduction, and adsorption have been used to remove radioactive cesium from aqueous solution. However, the development of innovative technologies capable of selectively removing radioactive cesium is still imperative yet challenging. This review focused on cesium removal using various separation technologies, including chemical precipitation, solvent extraction, membrane separation, and adsorption. The key restraints for cesium removal, as well as the recent progress of these methods have also been discussed. Particular attention has been paid to the adsorption methods, which has been highlighted by introducing the latest advances in inorganic adsorbents (such as metal hexacyanoferrates, clay minerals, carbon-based-adsorbents, and ammonium molybdophosphate), organic adsorbents (such as ion exchange resin, metal–organic frameworks and supramolecular/indicator grafting adsorbents), and biosorbents (such as agroforestry wastes and microbial biomass). Adsorption-based methods are high efficient in separation of cesium ions from aqueous streams, and adsorption of cesium ions has been investigated intensively and even used in practical applications, there is still considerable scope for improvement in terms of adsorption capacity and selectivity.